Primeri glagolske rabe z vidika posebnosti v slovnično-pomenskih razmerjih - Žele, Andreja (Slavistična revija, 2014)
Based on the examples of special or changed usage of verbs and some peculiarities in the usage in the predicate, the article highlights the mutual effect of verb categories in terms of the relationship grammar vs. lexicon. Some of the idiosyncrasies and changes in verb usage could be taken into consideration and reflected appropriately in the dictionary.
Keywords: dictionary; glagol; grammar; semantics; semantika; slovarji; Slovene; Slovenian language; slovenščina; slovnica; verb; verbal use